Resistance to Phytophthora infestans EC-1 clonal lineage in Solanum tuberosum by introducing the RB gene - Román, María Lupe (2015)
One of the most efficient options for the control of late blight disease in potato (Solanum tuberosum) is the development of resistant varieties to Phytophthora infestans mediated by the direct transfer of resistance (R) genes through genetic engineering. In the present work, we used Solanum bulbocastanum RB gene to confers broad spectrum resistance to P. infestans races. To that end, Agrobacterium - mediated genetic transformation was used to transform a susceptible potato variety, Desiree, with the binary vector pCIP68 harboring the RB gene. As a result, 19 transformed plants containing the RB gene were obtained. kanamycin resistance test and polymerase chain reaction (PCR) assays confirmed the integration of the T-DNA in the potato genome. The 19 transformed plants, also called transgenic events were subjected to infection under biosafety greenhouse conditions. Phytophthora infestans isolate POX067 of the EC-1 clonal lineage, commonly find in Peru, was used for the infection. Three of the 19 plants ([RB]54, [RB]56 and [RB]70) show high resistance levels to isolate POX067 of P. infestans.